Perancangan Preferensi Konsumen untuk Meningkatkan Kualitas Sabun Mandi Ramah Lingkungan Menggunakan QFD - Chriswahyudi Chriswahyudi; Wilda Fransisca (Universitas Teuku Umar, 2021)
Over time the wants and needs of consumers for a good or service always var. Understand that consumers are a very absolute obligation because consumers have diffent needs, desires and testes, so that the products to be offered must also be adjusted to the wants and needs of consumers. So that companies have to make new innovations or develop existing products so that the managed business will continue to survive. Due to product competition that accurs, companies must improve product quality in order to realize consumer desires. So that the soap industry must produce soap that is safe and of quality so as not to harm users. The purpose this research to be achieved is to determine the level of statisfaction of the variable consumers needs, the comparison of the relative importance (TKR) using the QFD method. From the HOQ matrix analysis, there are 12 variables of consumer desires and 12 variables of technical requirements for solid bath soap products. From the calculation of the improvement ratio value, it is found that 11 variables are in accordance with consumer desires (IR = 1) and 1 variable that is not in accordance with consumer desires because it has an IR value 0f 1.02 (IR>1) so that corrective action is needed. The technical requirements variable which is a priority has a value (3.897), variable the best meets consumer preferences has the greatest importance weight (TKK = 4.55)